Positive mood on the day of influenza vaccination predicts vaccine effectiveness: a prospective observational cohort study - Ayling, Kieran; Fairclough, Lucy; Tighe, Paddy; Todd, Ian; Halliday, Vanessa; Garibaldi, Jon; Royal, Simon; Hamed, Aljali; Buchanan, Heather; Vedhara, Kavita (Elsevier, 2017)
Influenza vaccination is estimated to only be effective in 17–53% of older adults. Multiple patient behaviors and psychological factors have been shown to act as ‘immune modulators’ sufficient to influence vaccination outcomes. However, the relative importance of such factors is unknown as they have typically been examined in isolation. The objective of the present study was to explore the effects of multiple behavioral (physical activity, nutrition, sleep) and psychological influences (stress, positive mood, negative mood) on the effectiveness of the immune response to influenza vaccination in the elderly. A prospective, diary-based longitudinal observational cohort study was conducted. One hundred and thirty-eight community-dwelling older adults (65–85 years) who received the 2014/15 influenza vaccination completed repeated psycho-behavioral measures over the two weeks prior, and four weeks following influenza vaccination. IgG responses to vaccination were measured via antigen microarray and seroprotection via hemagglutination inhibition assays at 4 and 16 weeks post-vaccination. High pre-vaccination seroprotection levels were observed for H3N2 and B viral strains. Positive mood on the day of vaccination was a significant predictor of H1N1 seroprotection at 16 weeks post-vaccination and IgG responses to vaccination at 4 and 16 weeks post-vaccination, controlling for age and gender. Positive mood across the 6-week observation period was also significantly associated with post-vaccination H1N1 seroprotection and IgG responses to vaccination at 16 weeks post-vaccination, but in regression models the proportion of variance explained was lower than for positive mood on the day of vaccination alone. No other factors were found to significantly predict antibody responses to vaccination. Greater positive mood in older adults, particularly on the day of vaccination, is associated with enhanced responses to vaccination.